Modeling vs. measuring: How accurate is the calculated maximal lactate steady state? - Sablain, M.; Vermeire, K.; Boone, J. (Journal of Science and Cycling, 2025)
Introduction The maximal lactate steady state (MLSS) represents the highest sustainable workload without net lactate accumulation. In 1986, Mader & Heck proposed a model estimating MLSS by determining the steady state oxygen consumption at the crossing point (VO2ss) between the rate of lactate formation and elimination. The sole input variables in this model are the VO2max and the maximal rate of blood lactate (BLa-) accumulation (VLamax) which is believed to represent the maximal glycolytic flux (Mader, 1994; Mader & Heck, 1986). Subsequently, an equation is often used to transform VO2ss into a power output using the resting oxygen consumption (VO2rest) and cycling efficiency (Kef). Previous research found no significant difference between the calculated power at MLSS (cPMLSS) and experimentally measured power at MLSS (mPMLSS) (Hauser et al., 2014). However, the Bland-Altman plots showed quite broad limits of agreements (LoA). It remains unclear if these broad LoA are caused by an error in the determination of VO2ss or the conversion into a power output as no prior studies have directly compared the measured (mVO2ss) and calculated VO2ss (cVO2ss). Therefore, this study wanted to compare mVO2ss and mPMLSS with cVO2ss and cPMLSS. Furthermore, we examined whether individualizing specific model constants (VO2rest and Kef) improved the LoA, potentially enhancing the model`s applicability.